Implementation of a pharmacogenomics consult service to support the INGENIOUS trial. Issue 1 (31st March 2016) - Eadon, MT; Desta, Z; Levy, KD; Decker, BS; Pierson, RC; Pratt, VM; Callaghan, JT; Rosenman, MB; Carpenter, JS; Holmes, AM; McDonald, CA; Benson, EA; et al.
Abstract : Hospital systems increasingly utilize pharmacogenomic testing to inform clinical prescribing. Successful implementation efforts have been modeled at many academic centers. In contrast, this report provides insights into the formation of a pharmacogenomics consultation service at a safety‐net hospital, which predominantly serves low‐income, uninsured, and vulnerable populations. The report describes the INdiana GENomics Implementation: an Opportunity for the UnderServed (INGENIOUS) trial and addresses concerns of adjudication, credentialing, and funding.